Effectiveness of Fluoride Varnish Application as Cariostatic and Desensitizing Agent in Irradiated Head and Neck Cancer Patients - Kanchan P. Dholam; Priyanka Piyush Somani; Seema D. Prabhu; Shubhangi R. Ambre (International Journal of Dentistry)
Objective. To evaluate the effectiveness of three-month fluoride varnish application on radiation caries and dental sensitivity and to assess compliance to three-month fluoride varnish application. Materials and Methods. 190 irradiated head and neck cancer patients were randomly selected and reviewed retrospectively. Oral prophylaxis, fluoride varnish application, and treatment of dental caries were done prior to radiation therapy. Patients were followed up at every three months for dental evaluation and fluoride varnish application. Decayed-missing-filling-teeth indices, dental sensitivity, and compliance to fluoride varnish application were noted for fifteen months and analyzed statistically. Results. Significant increase in decayed-missing-filling-teeth index was seen at nine (P=0.028), twelve (P=0.003) and fifteen (P=0.002) months follow-up. However, the rate of increase in decayed-missing-filling-teeth indices was 1.64/month which is less than the rate mentioned in the literature (2.5/month). There was no significant effect of sex (P=0.952) and surgery (P=0.672) on radiation caries, but site of disease (P=0.038) and radiation dose (P=0.015) were found to have statistically significant effect. Dental sensitivity decreased from 39% at 3 months to 25% at 15 months followup. 99% compliance to fluoride varnish application was seen till six months followup which decreased to 46% at fifteen months. Conclusion. Three-month fluoride varnish application is effective in decreasing radiation caries and sensitivity and has good compliance.